TRANSFORMASI MAKNA AL-ṬAYR DALAM QS. AL-MULK [67]:19: Aplikasi Semiotika Roland Barthes - Balqis, Putroe; Unzila, Alifia Rizqa (Jurnal Studi Islam dan Sosial, 2025)
In the tafsir tradition, al-ṭayr carries a high spiritual meaning because it is able to show the oneness of Allah. But in a broader context, the word al-ṭayr can refer to human fate, deeds, or responsibilities. This transformation of meaning indicates that birds are not only biological creatures but also spiritual symbols that implicitly describe the journey of human life. But often, humans are caught up in the routine of worldly activities that are far from the ideals taught in the qur’an. This study aims to complement the shortcomings of previous research and to enrich the intellectual treasure by presenting a different perspective on the meaning of al-ṭayr in QS. al-Mulk [67]:19. This article is qualitative research with a library research model. This research uses primary data obtained from the Qur’an and classical and contemporary books of tafsir. While secondary data sources are obtained from reading literature related to the problem. The approach used in this research uses Roland Barthes’ semiotic approach. As for the result of the research, the word al-tayr not only reflects physical symbolism but also describes the relationship between human efforts and God’s destiny, which is always tied to the last day.